Cerebro- and Cardio-vascular Responses to Energy Drink in Young Adults: Is there a Gender Effect? - Monnard, Cathríona R.; Montani, Jean-Pierre; Grasser, Erik K. (Frontiers in Physiology, 2016)
Background and Purpose: Energy drinks (EDs) are suspected to induce potential adverse cardiovascular effects and have recently been shown to reduce cerebral blood flood velocity (CBFV) in young, healthy subjects. Gender differences in CBFV in response to EDs have not previously been investigated, despite the fact that women are more prone to cardiovascular disturbances such as neurocardiogenic syncope than men. Therefore, the aim of this study was to explore gender differences in cerebrovascular and cardiovascular responses to EDs. Methods: We included 45 subjects in a retrospective analysis of pooled data from two previous randomized trials carried out in our laboratory with similar protocols. Beat-to-beat blood pressure, impedance cardiography, transcranial Doppler, and end-tidal carbon dioxide (etCO2) measurements were made for at least 20 min baseline and for 80 min following the ingestion of 355 mL of a sugar-sweetened ED. Gender and time differences in cerebrovascular and cardiovascular parameters were investigated. Results: CBFV was significantly reduced in response to ED, with the greatest reduction observed in women compared with men (-12.3 ± 0.8 vs. -9.7 ± 0.8 %, P < 0.05). Analysis of variance indicated significant time (P < 0.01) and gender x time (P < 0.01) effects. The percentage change in CBFV in response to ED was independent of body weight and etCO2. No significant gender difference in major cardiovascular parameters in response to ED was observed. Conclusions: ED ingestion reduced CBFV over time, with a greater reduction observed in women compared with men. Our results have potential implications for women ED consumers, as well as high-risk individuals.